An expert consensus–based checklist for quality appraisal of educational resources on adult basic life support: a Delphi study - Alexei Birkun; Adhish Gautam; Bernd W. Böttiger; the Delphi Study Investigators (Clinical and Experimental Emergency Medicine, 2023)
Objective Given the lack of a unified tool for appraising the quality of educational resources for lay-rescuer delivery of adult basic life support (BLS), this study aimed to develop an appropriate evaluation checklist based on a consensus of international experts. Methods In a two-round Delphi study, participating experts completed questionnaires to rate each item of a predeveloped 72-item checklist indicating agreement that an item should be utilized to evaluate the conformance of an adult BLS educational resource with resuscitation guidelines. Consensus on item inclusion was defined as a rating of ≥7 points from ≥75% of experts. Experts were encouraged to add anonymous suggestions for modifying or adding new items. Results Of the 46 participants, 42 (91.3%) completed the first round (representatives of 25 countries with a median of 16 years of professional experience in resuscitation) and 40 (87.0%) completed the second round. Thirteen of 72 baseline items were excluded, 55 were included unchanged, four were included after modification, and four new items were added. The final checklist comprises 63 items under the subsections “safety” (one item), “recognition” (nine items), “call for help” (four items), “chest compressions” (12 items), “rescue breathing” (12 items), “defibrillation” (nine items), “continuation of CPR” (two items), “choking” (10 items) and “miscellaneous” (four items). Conclusion The produced checklist is a ready-to-use expert consensus–based tool for appraising the quality of educational content on lay-rescuer provision of adult BLS. The checklist gives content developers a tool to ensure educational resources comply with current resuscitation knowledge, and may serve as a component of a prospective standardized international framework for quality assurance in resuscitation education.